Challenges that impact youth engagement with batik industries on social media - Mohd Salleh Anuar, Nur Nadia; Abdul Latiff, Dzaa Imma; Mohd Fathir, Mohd Firdaus (‘Abqari Journal, 2025)
Batik, a traditional textile art form originating from Southeast Asia, particularly Malaysia and Indonesia, holds significant historical and cultural value. However, it is currently struggling to engage younger generations, especially on popular social media platforms like Instagram and TikTok. This study explores the socio-economic and digital barriers that limit youth participation and interaction with Batik content online. One major challenge is the digital divide among youth from rural or low-income backgrounds, many of whom lack access to smartphones and stable internet connections. Even when digital tools are available, a lack of digital literacy often prevents effective use of social media for engaging with Batik content. These factors significantly hinder youth from discovering, appreciating, or promoting Batik in the digital realm. The industry also faces issues in portraying Batik as relevant and versatile for modern fashion and daily wear. Without targeted efforts to bridge digital and social gaps, Batik risks being viewed as outdated or relegated solely to ceremonial use. To ensure Batik remains a vibrant part of Southeast Asian heritage, the industry must adopt inclusive strategies. These include improving digital literacy, enhancing access to technology, and creating youth-oriented, relatable content that highlights Batik's modern appeal. By addressing these barriers, Batik can remain both a symbol of cultural identity and a fashionable, contemporary choice embraced by future generations.